Impact of screen exposure on pediatric vernal Keratoconjunctivitis: a survey during the COVID-19 pandemic in Italy - Marzio Masini; Giulia Brindisi; Mattia Giovannini; Elia Pignataro; Laura Di Grande; Cinzia De Libero; Marcella Nebbioso; Francesca Mori; Roberto Caputo; Anna Maria Zicari (BMC, 2022)
Abstract Background The SARS-CoV-2 outbreak pushed the Italian government to start a strict lockdown, replacing school attendance with long-distance learning. This caused reduced exposure to sunlight but increased exposure to screens. Vernal keratoconjunctivitis (VKC) is a chronic inflammatory ocular condition in which exposure to light plays a cardinal role. We conducted an online survey to evaluate the impact of screen exposure on children with VKC during the COVID-19 lockdown. Methods We performed a survey-based observational study, asking patients followed at the Allergology clinics of Meyer Children's University Hospital in Florence and of Policlinico Umberto I in Rome to provide grading on 6 subjective ocular clinical manifestations presented during the lockdown and to give an estimate of their hours/day of screen exposure. Results Mean scores of signs and symptoms increased homogeneously when studying patients exposed to longer screen time. When comparing scores collected in 2019 to those in 2020, there was not a significant reduction in clinical manifestations, although the situation differed between the two centers due to geographical differences in sunlight exposure. Conclusion During the lockdown, there was a reduction in sunlight exposure but conversely an increase in the time spent in front of screens that correlated with the worsening of VKC signs and symptoms in direct proportion to the hours/day of screen exposure. Our results also showed a statistically significant difference in the relative impact of long-distance learning on VKC clinical manifestations in the different Italian regions.